2017
DOI: 10.1016/j.drugalcdep.2017.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with SCRAMx alcohol monitoring technology in 100 alcohol treatment outpatients

Abstract: Background Transdermal alcohol monitoring technology allows for new research on alcohol use disorders. This study assessed feasibility, acceptability, and adherence with this technology in the context of two clinical research trials. Methods Participants were the first 100 community-based alcohol treatment outpatients enrolled in randomized studies that monitored drinking with the secure continuous remote alcohol monitor (SCRAMx®) for 12 weeks. Study 1 participants were randomized to usual care (n=36) or usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 43 publications
(49 reference statements)
2
70
0
Order By: Relevance
“…TAS field studies have been conducted in various populations, including college students and young adults (e.g., Luczak et al., ; Neville et al., ), treatment‐seeking (e.g., Barnett et al., ), and non–treatment‐seeking heavy drinkers recruited from the community (Dougherty et al., ,b), outpatients from alcohol treatment facilities (Alessi et al., ), and adults recently arrested for driving under the influence of alcohol (e.g., Mathias et al., ). Investigations using WrisTAS have typically involved wearing the device for 1 to 2 weeks (Luczak et al., ; Marques and McKnight, ; Simons et al., ).…”
Section: Transdermal Alcohol Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…TAS field studies have been conducted in various populations, including college students and young adults (e.g., Luczak et al., ; Neville et al., ), treatment‐seeking (e.g., Barnett et al., ), and non–treatment‐seeking heavy drinkers recruited from the community (Dougherty et al., ,b), outpatients from alcohol treatment facilities (Alessi et al., ), and adults recently arrested for driving under the influence of alcohol (e.g., Mathias et al., ). Investigations using WrisTAS have typically involved wearing the device for 1 to 2 weeks (Luczak et al., ; Marques and McKnight, ; Simons et al., ).…”
Section: Transdermal Alcohol Sensorsmentioning
confidence: 99%
“…One study using WrisTAS reported that 6% of college student participants failed to consistently wear the sensor (Luczak et al., ), and another study involving students found that the sensor was removed on approximately 10% of all study days (Simons et al., ). In a clinical sample using SCRAM devices, 34% of participants tampered with the sensor, and 56% of these tamper events were linked to drinking (Alessi et al., ).…”
Section: Transdermal Alcohol Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of alcohol permeating through the epidermis in this manner can be detected by wearable devices, termed transdermal sensors, and has exhibited validated correlations against BrAC and BAC (Figure 1A) [4446]. Several sensing platforms utilizing this method of alcohol monitoring have been developed with most clinical reports focusing on two devices: the Secure Continuous Remote Alcohol Monitor from Alcohol Monitoring Systems, Inc. (SCRAM™; Figure 4A); and the Wrist Transdermal Alcohol Sensor from Giner Inc. (WrisTAS™; Figure 4B) [4648]. The SCRAM™ is designed as an ankle bracelet with a sensor compartment and a digital signal processing compartment, which transmits the collected data to an in-home modem.…”
Section: Transdermal Alcohol Monitoring Platformsmentioning
confidence: 99%
“…Despite these drawbacks, efforts to introduce the SCRAM offender-monitoring bracelet into alcohol addiction treatment were encouraging, with a large majority (81%) of wearers reporting the bracelet to be useful in helping them reduce drinking, although social discomfort and physical irritation was observed, related to the physical shape and size of the bracelet. [22,23].…”
Section: Introductionmentioning
confidence: 99%